U-Shaped Concrete Drain Containing Rice Husk Ash as Partial Cement Replacement by Using Non-Autoclaved Aerated Technique - Ang, Zi Jian; Dr. Hamidun bin Mohd Noh (Research in Management of Technology and Business, 2022)
Concrete is the most widely used material in the world which increases the demand for cement as the main material. Hence, a huge amount of cement is manufactured to fulfill the demand and contribute to serious carbon emissions. However, the materials used for the concrete have been extensively modified to increase the durability and aesthetic value. Rice husk ash (RHA) is one of the alternative materials for cement replacement due to the pozzolanic behaviour which consists of 85%-90% silica.  The objectives of this research are to determine the optimum percentage of RHA as partial cement replacement in concrete, to compare the compressive strength of the RHA concrete with the standard concrete cube, to compare the compressive strength of RHA non-autoclaved aerated concrete (NAAC) drain with standard drain and to determine the durability performance of RHA NAAC drain in normal environment. There are five cube specimens were cast to identify the optimum percentage and one RHA NAAC drain was cast to conduct a rebound hammer test according to BS 1881-202. After the experiment, the optimum percentage RHA is identified in 10% with 11.9 MPa compressive strength. Besides that, the compressive strength of RHA NAAC drain is 12.67 MPa compressive strength. The purpose of this research is to apply RHA to reduce the usage of cement as well as reduce carbon emissions. Furthermore, using NAAC technique in the drain can reduce the cost of the project in the progress of installation and delivery.